Citrus Polyphenols in Brain Health and Disease: Current Perspectives - Pontifex, Matthew G.; Malik, Mohammad M. A. H.; Connell, Emily; Müller, Michael; Vauzour, David (Frontiers in Neuroscience, 2021)
In addition to essential micronutrients such as vitamin C, citrus fruits represent a considerably rich source of non-essential bioactive compounds, particularly flavanones which form a sub-set of the flavonoids group. Preclinical studies have highlighted the neuroprotective potential of citrus flavonoids, with well-established anti-oxidative, anti-inflammatory and newly emerging blood-brain barrier function/integrity mechanistic actions providing an explanation for their potential in modifying risk of neurological disease. Encouragingly, results from human studies, although limited in number, appear to support this preclinical basis, with improvements in cognitive performance and disease risk observed across healthy and disease states. Therefore, citrus fruits – both as whole fruit and 100% juices - should be encouraged within the diet for their potential neurological benefit. In addition, there should be further exploration of citrus polyphenols to establish therapeutic efficacy, particularly in the context of well-designed human interventions.